Penerapan PSAK 69 terhadap perlakuan akuntansi dan deplesi aset biologis - Anggraini, Desy Ismah (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this study was to determine the implementation of accounting treatment and depletion of biological assets based on PSAK 69 which was applied to UD Ternak Mandiri. Biological assets are different from fixed assets which are always shrinking, the value of biological assets will always grow. Due to these unique characteristics, biological assets must be treated differently from other assets such as land, buildings, and others. IAS 41 on agriculture was subsequently adopted into PSAK 69 on Agriculture which came into effect on January 1, 2018 which has a different method of calculating biological assets and depletion. This research was conducted with a case study approach by conducting direct observations, interviews, and documentation. The accounting treatment of biological assets at UD Ternak Mandiri is similar to the accounting treatment of fixed assets in the form of land. UD Ternak Mandiri has measured biological assets in accordance with PSAK 69, and in relation to the death or disability of biological assets, UD livestock Mandiri has not made any adjustments that cause the book value to differ from the actual value.